Incentivo fiscal e desenvolvimento regional no estado de Mato Grosso : análise do Programa de Incentivo à Cultura do Algodão - PROALMAT no período de 1997 a 2007 - Miranda, Zelma Beatriz Paz (2012)
New routes in territorial public policy development indicate changes in the regional policy paradigm, conforming to the reorganization of geographic space, with the substitution of traditional instruments. In this context, fiscal incentives public policy has emerged as an alternative as much at the federal as at the state governmental level for local and regional development. As part of this process the state has assumed the role of main inductor and mobiliser of economic and social agents in the planning, formulation, execution and evaluation of public policies concerned with regional development. In Brazil, fiscal incentives have been applied on a large scale at the federal, state and municipal level. Mato Grosso has a part in this, because it has been taking advantage of fiscal incentives public policy for the promotion of economic and social development. This being the case, this dissertation investigated if fiscal incentives public policy in the state of Mato Grosso is in fact based upon effective regional development or is based only upon economic development. To understand the context the main aspects of the management cycle of this particular public policy were analyzed, the legislation in which it was based, its instruments and its budgetary and financial information. The Cotton Growing Incentives Programme - PROALMAT, of agriculture awarded by the Mato Grosso state government since 1997 will be presented as a case study. The research presented here and based upon the specific study of cotton growing incentives public policy was carried out by taking an exploratory-type approach, with the utilization of documentary sources and semi-structured interviews. Empirical observation was systematized by examination of legal documents (laws and decrees); bibliographical research was also carried out in which took the form of a literature review and the collating of relevant sources.